Performan Produksi dan Kapasitas Suplay Sapi Bali Bibit dan Potong di Kabupaten Lombok Barat, Nusa Tenggara Barat - M Ashari; Lalu Wirapribadi; Rr. Agustien Suhardiani; Happy Poerwoto; Rina Andriati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
This research was conducted in West Lombok Regency with the aim of knowing the production performance and supply capacity of Bali cattle seeds and beef in West Lombok district. The research was conducted by survey method. The research sample consisted of farmers and the livestock they kept. This research was conducted in two sub-districts and three sample villages were selected for each sub-district. The number of samples is 60 farmer respondents. The variables observed included body weight, body size, birth rate, mortality rate, calf harvest, calving period and age of rejection. The data collected were analyzed descriptively. To determine the level of production and supply capacity of Bali cattle, seeds and cuts, the data were analyzed using Dania guidelines. Structure The population of Bali cattle consists of 33.33% calves, 21.21% young and 45.45% adults with a child harvest rate of 26.97% and a mortality rate of 2.49% of the population. The average body weight of Bali cattle in West Lombok Regency, weaning calf, young and adult, respectively, is 129.65, 247.98 and 275.75 kg adults with gumba height, 99.08 weaning calves, 112.75 young and adults 118.45 cm. The supply capacity of breeder cattle and beef cattle in West Lombok Regency is 24.28% of the population, consisting of 6.51% beef cattle and 17.76% breed cattle.